Effect of ambient noise reduction on speech recognition and listening effort in noise in MED-EL cochlear implant users. - Müller, Verena; Ukuwait, Amanuel; Frößler, Katrin; Lang-Roth, Ruth (International Journal of Audiology, 2025)
Objective: This study investigated whether the SONNET 2 audio processor's ambient noise reduction (ANR) algorithm improves speech recognition and listening effort in cochlear implant (CI) users as a function of different noise signals. Design: Speech recognition and listening effort were measured in the presence of four different noise signals, including stationary and fluctuating noise, and including a speech masker. Speech was presented from the front (S0) and noise from two sources from the back (N ± 135). Study sample: 20 adult CI users. Results: With the ANR, speech recognition significantly improved in the presence of one stationary noise and in the presence of one fluctuating noise. The ANR had no significant effect on listening effort. Conclusions: When activating the ANR algorithm of the SONNET 2 audio processor, speech recognition improved in some conditions. Listening effort was equal in all conditions. In corresponding everyday situations, it can be recommended to use the ANR algorithm.